2009
DOI: 10.1007/s00383-009-2480-1
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of erythropoietin on the acute phase of corrosive esophageal burns in a rat model

Abstract: When administered early after an esophageal burn induced by 10% sodium hydroxide in this rat model, erythropoietin significantly attenuated oxidative damage, as measured by biochemical markers and histologic scoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 93%
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 93%
“…Research has focused on the healing of the burned esophagus and reduction in collagen formation [9,10]. In animal experiments, a variety of different medications, such as erythropoietin, caffeic acid phenethyl ester, mitomycin C, ketotifen, and resveratrol have been used in attempt to prevent esophageal stricture formation after caustic ingestion [6][7][8][9][10]. We investigated the role of dexpanthenol and Y-27632, two different agents with different modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids, antibiotics, proton pump inhibitors, and H 2 receptor blockers are widely used in an effort to prevent stricture formation [1,4,5]. Ongoing experimental research continues to attempt to identify novel treatment strategies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…EPO is a strong antioxidant (6), and it has been reported that EPO in crea sed the acti vi ty of antioxidant enzymes and de creased lipid per oxi dation (14,15). Furthermore, Bakan et al (16) sug gested that there was a direct relationship bet ween the levels of antioxidant enzymes and lipid peroxidation. In this study, EPO treatment increased TAC and PONX le vels and decreased TOA levels.…”
Section: Discussionmentioning
confidence: 99%